Intraspecific trait variation in a dryland tree species corresponds to regional climate gradients. (19th October 2022) - Vasey, Georgia L.; Weisberg, Peter J.; Urza, Alexandra K.
Abstract: Aim: Intraspecific trait variation is fundamental to understanding a species' adaptive capacity. Assessing phenotypic variation at different ecological scales is useful for evaluating species' vulnerability to changing environmental conditions. Here, we quantify the ecological scale of variation of phenotypic functional traits for a widespread dryland tree species and evaluate the strength of trait‐environment relationships across spatial gradients and in response to interannual variability in weather conditions. Location: Western United States. Taxon: Conifer tree (Pinaceae): Pinus monophylla . Methods: Nine reproductive and foliar morphological traits were measured from 23 sampling locations in nine mountain ranges, stratified across broad‐scale gradients of precipitation timing and quantity and local gradients of elevation. We partitioned trait variation within and among nested ecological scales (mountain range, site, tree, and tree growth year). We then used multivariate methods to quantify the association between environmental variables and ecological trade‐offs associated with both reproductive and foliar traits. Results: Most variation was explained at the scale of individual trees (18%–46%) and between growth years (20%–30%), with smaller but variable contributions at the scale of sites (8%–25%) and mountain ranges (0%–15%). Trait values had low correlation with environmental variables (13%); however, 94% of the trait‐environment covariance was explained by two major axes of variation: (1) the drought‐stress gradient covarying with reproductive traits, and (2) precipitation patterns covarying with foliar morphology. Main conclusions: High levels of individual trait variation indicate within‐population adaptive capacity. Consistent relationships among range‐wide patterns of foliar and reproductive traits and broad‐scale climate gradients provide indirect evidence of local adaptation and may inform seed sourcing for restoration or the potential for assisted migration efforts. Quantification of intraspecific trait variation across multiple ecological scales is important for understanding the potential climate change response of dryland tree species.